Helminth Infection During Pregnancy and Development of Infantile Eczema - Elliott, Alison M.; Mpairwe, Harriet; Quigley, Maria A.; Nampijja, Margaret; Muhangi, Lawrence; Oweka-Onyee, James; Muwanga, Moses; Ndibazza, Juliet; Whitworth, James A. G. (American Medical Association, 2005)
The burden of atopic and inflammatory disease is escalating in developed countries, in inverse relation to infectious diseases.1 Mechanisms by which exposure to infections may promote balanced immunological development are being explored2 and trials of therapeutic helminth parasites have been initiated for asthma and inflammatory bowel disease.3,4 In developing countries, advocacy for deworming is increasing, and treatment with anthelmintics targeting hookworm anemia is recommended after the first trimester of pregnancy.5-7 During a trial8 to determine the effects of deworming during pregnancy on immune responses and infectious disease incidence in infants, we noted an unexpectedly high incidence of infantile eczema. Therefore, we examined associations between maternal helminth parasites and deworming and infantile eczema.
Keywords: Helminth Infection; Pregnancy; Infantile Eczema